Collapsed Ricci Limit Spaces as Non-Collapsed RCD Spaces - Honda, Shouhei (Symmetry, Integrability and Geometry: Methods and Applications, 2020)
In this short note, we provide several conjectures on the regularity of measured Gromov-Hausdorff limit spaces of Riemannian manifolds with Ricci curvature bounded below, from the point of view of the synthetic treatment of lower bounds on Ricci curvature for metric measure spaces.